Закономірності взаємодії інтонації в мовленні та музиці - Марченко, Валентина Володимирівна; Marchenko, V. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено висвітленню проблеми взаємозв’язку інтонації мовлення та музики, зокрема проілюстровано ступінь вивчення цього питання науковцями різних галузей (музикознавцями, лінгвістами, психологами та ін.), з’ясовано значення терміна «інтонація» для обох семіотичних систем. На основі зіставного аналізу наявних у лінгвістиці наукових знань виявлено спільний для інтонації мовлення й музики комплекс компонентів інтонації та виокремлено відмінні ознаки музичної інтонації. Указано на перспективність подальшоговивчення взаємодії інтонації мовлення та музики в мовленнєво-музичних творах. The article focuses on the problem of the interrelation between speech and music intonation, particularly highlighting the issue from the point of view of scientists in various fields (musicologists, linguists, psychologists etc.), defining the meaning of the term «intonation» for both semiotic systems, and attempting to prove the assumption of primacy of speech over music. Basing on comparative analysis of the existing scientific knowledge in linguistics the author ascertains the complex of intonation components common for both speech and music including melody, stress, rhythm, tempo, pause, and timbre, and defines the features inherent in music intonation only. Further study of the interrelation between speech and music intonation is considered most promising in regard to speech-music compositions.
Regularities of the Interrrelation Between Speech and Music Intonation
Keywords: мовлення; speech; музика; music; компоненти інтонації; intonation components